Transduction Efficiency and Immunogenicity of Viral Vectors for Cochlear Gene Therapy: A Systematic Review of Preclinical Animal Studies - Verdoodt, Dorien; Peeleman, Noa; Van Camp, Guy; Van Rompaey, Vincent; Ponsaerts, Peter (Frontiers in Cellular Neuroscience, 2021)
Background: Hearing impairment is the most frequent sensory deficit, affecting 466 million people worldwide and has been listed by the World Health Organization (WHO) as one of the priority diseases for research into therapeutic interventions to address public health needs. Inner ear gene therapy is a promising approach to restore sensorineural hearing loss, for which several gene therapy applications have been studied and reported in preclinical animal studies. Objective: To perform a systematic review on preclinical studies reporting cochlear gene therapy, with a specific focus on transduction efficiency. Methods: An initial PubMed search was performed on April 1st 2021 using the PRISMA methodology. Preclinical in vivo studies reporting primary data regarding transduction efficiency of gene therapy targeting the inner ear were included in this report. Results: Thirty-six studies were included in this review. Transduction of various cell types in the inner ear can be achieved, according to the viral vector used. However, there is significant variability in the applied vector delivery systems, including promoter, viral vector titer, etc. Conclusion: Although gene therapy presents a promising approach to treat sensorineural hearing loss in preclinical studies, the heterogeneity of methodologies impedes the identification of the most promising tools for future use in inner ear therapies.